Differences in tumour characteristics of Hepatocellular Carcinoma between patients with and without Cirrhosis: A population-based study - Yan, Bing (J Cancer, 2020)
Background: Liver cirrhosis is a major risk factor for hepatocellular carcinoma (HCC). However, 10%-20% of patients with HCC do not have cirrhosis. The aim of this study was to explore the potential differences in tumour characteristics of HCC between patients with and without cirrhosis. Methods: In this study, we identified total 10,849 patients with HCC diagnosed between 2010 and 2016, from the SEER database. The degree of fibrosis was categorized as “no cirrhosis” (Ishak score 0-4) or “cirrhosis” (Ishak score 5-6). Among all patients with HCC, patients with no cirrhosis and with cirrhosis accounted for 1800 (16.6%) and 9049 (83.4%), respectively. Results: Significant negative correlations were observed between no cirrhosis/cirrhosis and pathological grade (r =-0.074, P <0.001), tumour size (r =-0.186, P <0.001), N stage (r =-0.024, P =0.025), M stage (r =-0.036, P <0.001), liver metastasis (r =-0.024, P =0.014), and lung metastasis (r =-0.027, P =0.006). Logistic multivariate regression analysis showed that, compared with cirrhosis, no cirrhosis is an independent risk predictor of pathological grade [odds ratio (OR), 0.685; 95% confidence interval (CI), 0.571-0.822; P < 0.001], tumour size (OR, 0.392; 95% CI, 0.351-0.437; P < 0.001), N stage (OR, 0.704; 95% CI, 0.561-0.883; P < 0.001), and M stage (OR, 0.671; 95% CI, 0.561-0.804; P < 0.001). Conclusions: Compared with cirrhosis, no cirrhosis is significantly associated with worse pathological grade, larger tumour size, and more lymph node and distant metastases. Patients without cirrhosis that are otherwise neglected in HCC clinical practice require intensive focus in future studies.